Cognitive Depletion and Its Effect on Decision Making - Farská, Kateřina (2013)
One of the factors significantly influencing our daily decisions is the so-called cognitive depletion.The theory of cognitive depletion postulates the existence of a limited mental resource that is necessary for self-regulation. If the resource is diminished by a task involving self-control, achievement in subsequent self-control task will be impaired. This project examines the effect of cognitive depletion on decisions in the Iowa Gambling Task designed to simulate real-life decision making involving gains and losses. Further, a possible effect of moderating factors that could be affected by cognitive depletion and consequently influence decisions in the Iowa Gambling Task -- risk preference and impulsivity -- is investigated. Dual-process theories postulate there are two systems involved in decision-making: faster, intuitive, emotional System 1 and slower, deliberative, rational System 2. It was found that cognitive depletion leads to enhancement of System 1. As advantageous decisions in the Iowa Gambling Task are closely related to emotional reactions -- domain of System 1 -- it was hypothesized that cognitive depletion will lead to not worse, or possibly even better results in depleted subjects. A controlled laboratory experiment was conducted involving 39 subjects in total. No difference was found in average desicions of depleted and non-depleted subjects in the Iowa Gambling Task, supporting the hypothesis. Further, short-term increase in impulsivity caused by cognitive depletion was very probably moderating choices in the IGT, leading to worse overall performance. Regarding risk preferences, we found that non-depleted subjects were generally more risk seeking in losses context, while depleted subjects exhibited rather loss aversion. This change in risk behaviors due to cognitive depletion very probably did not mediate choices in the Iowa Gambling Task.